Impelementasi Sistem Presensi Wisuda Berbasis QR Code untuk Meningkatkan Layanan Menggunakan MERN Stack - Puja Hanifah; Felly Chandra; Dini Hidayatul Qudsi; Meilany Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Graduation is a ceremonial activity routinely conducted at a university, including at Polytechnic Caltex Riau. The process of conferring degrees at Polytechnic Caltex Riau has been experiencing an increase each year. In the registration process, a website has already been used to facilitate the registration, but on the implementation day, it is still done manually. Like the attendance process for graduates still using paper, as well as parents who must sign in when they arrive. This takes a long time in the process, not to mention the loss of attendance records, duplicate signatures, and so on. Because of these issues, a graduation attendance system was built that will use QR codes in the registration process and was developed using MERN Stack technology. The purpose of developing this system is to facilitate the graduation committee in coordinating activities with parents and graduates. The use of MERN Stack technology is very suitable for development for real-time data, and using QR codes speeds up the existing process. From the research results, all features of the system are operational and can be used based on the UAT testing conducted on three users, namely the admin, super admin, and BAAK. The usability testing yielded a score of 63%, indicating that the system is somewhat difficult to use and the interface needs further improvement.